HUBUNGAN TINGKAT MINDFUL EATING DENGAN KEJADIAN OBESITAS PADA REMAJA DI SMAN 5 KOTA DEPOK - Zulfa Nur Latifah Choirunnisa, (2022)
Obesity can be experienced by all age groups, including adolescents. Obesity in adolescents can be caused by various factors, like changes in eating behaviour and psychological factors. External influences can affect adolescents when eating which make them less aware of the activity and adolescents have higher risk to experience stress which leads to emotional eating, so the amount of intake increased. This shows low level of mindful eating. Mindful eating in its application, can make a person consume food as needed and not excessive. People with low level of mindful eating tend to have a higher BMI. The purpose of this study was to determine the relationship between mindful eating level with obesity in adolescents in SMA N 5 Depok City. The research method used was quantitative approach with a cross-sectional design. The study population was male and female students of class X and XI at SMA Negeri 5 Kota Depok with a research sample of 60 respondents and used a simple random sampling technique. The data analysis in this study used the chi square statistical test. The results of the bivariate data analysis showed that there was relationship between mindful eating level ( p = 0,000) and obesity on students in class X and XI SMA Negeri 5 Kota Depok.